Validation of an MRI brain injury and growth scoring system in very preterm infants scanned at 29-to 35-week postmenstrual age - George, J.; Fiori, S.; Fripp, J.; Pannek, K.; Bursle, J.; Moldrich, R.; Guzzetta, A.; Coulthard, A.; Ware, R.; Rose, S.; Colditz, P.; Boyd, Roslyn (American Society of Neuroradiology, 2017)
Background and Purpose: The diagnostic and prognostic potential of brain MR imaging before term-equivalent age is limited until valid MR imaging scoring systems are available. This study aimed to validate an MR imaging scoring system of brain injury and impaired growth for use at 29 to 35 weeks postmenstrual age in infants born at < 31 weeks gestational age. Materials and Methods: Eighty-three infants in a prospective cohort study underwent early 3T MR imaging between 29 and 35 weeks' postmenstrual age (mean, 32 +2 ± 1 +3 weeks; 49 males, born at median gestation of 28 +4 weeks; range, 23 +6 -30 +6 weeks; mean birthweight, 1068±312 g). Seventy-seven infants had a secondMRscan at term-equivalent age (mean, 40 +6 ±1 +3 weeks). Structural images were scored using a modified scoring system which generated WM, cortical gray matter, deep gray matter, cerebellar, and global scores. Outcome at 12-months corrected age (mean, 12 months 4 days ± 1 +2 weeks) consisted of the Bayley Scales of Infant and Toddler Development, 3rd ed. (Bayley III), and the Neuro-Sensory Motor Developmental Assessment. Results: Early MR imaging global, WM, and deep gray matter scores were negatively associated with Bayley III motor (regression coefficient for global score ß =-1.31; 95% CI,-2.39 to-0.23; P = .02), cognitive (ß =-1.52; 95% CI,-2.39 to-0.65; P < .01) and the Neuro-Sensory Motor Developmental Assessment outcomes (ß =-1.73; 95% CI,-3.19 to-0.28; P = .02). Early MR imaging cerebellar scores were negatively associated with the Neuro-Sensory Motor Developmental Assessment (ß =-5.99; 95% CI,-11.82 to-0.16; P = .04). Results were reconfirmed at term-equivalent-age MR imaging. Conclusions: This clinically accessible MR imaging scoring system is valid for use at 29 to 35 weeks postmenstrual age in infants born very preterm. It enables identification of infants at risk of adverse outcomes before the current standard of term-equivalent age.